Prinsip-Prinsip dan Teknik Evaluasi dalam Pendidikan Agama Islam - Parahita, Dwisiwi Hardani; Setiyatna, Hery (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Evaluation is one component of the education system that must be carried out systematically and in a planned manner as a tool to measure success or targets to be achieved in the education process or learning process. Evaluation can provide a more comprehensive approach in providing information to education to help improve and develop the education system. However, not all educators have implemented effective and efficient evaluation optimally. Through the literature study method, it is expected to provide information on the principles and techniques of Islamic Religious Education evaluation to increase the insight and competence of educators in the field of evaluating learning outcomes, especially Islamic Religious Education. The principles of evaluation include the principles of integration, student involvement, coherence, pedagogy and accountability, in addition to including the principles of continuity, comprehensiveness, objectivity, and practicality. The principle of Islamic Religious Education evaluation is to determine the level of success in achieving the goals of Islamic education, namely fostering an Islamic personality through the application of integrated and comprehensive learning evaluation. Evaluation techniques that can be applied in Islamic Religious Education are test and non-test techniques to determine the development of aspects of aqliyah, qolbiyah, and amaliyah.